Male fertility restoration of rye crosses in the pampa cytoplasm. - Kolasiñska, Irena (Plant Breeding and Seed Science, 2003)
Male fertility restoration of F1 crosses between male sterile lines (P lines) and restorers (R) was studied in 2000. Pollen fertility of 50 F1 crosses derived by crossing 10 P lines to 5 restorers was estimated. The degree of male sterility/fertility was assessed by visual anther score of single plants on a 1-9 scale, restorer indices and visual pollen shedding scores of plots on a 1-9 scale. @Abstract = Coefficients of correlation between the above fertility traits were calculated. The analysis of variance showed that the degree of male fertility of F1 crosses strongly depends on a restorer genotype, a P line genotype as well as on the P ´ R interaction. The restorer and P line genotypes were a major source of variation.A considerable range of pollen fertility was evident in the single crosses. The mean restorer index of F1 crosses ranged from 3,4 to 98,7%. The P lines under study were divided into three groups on the basis of mean restorer indices of their crosses with five restorers: easy, medium and difficult to restore. All the restorers tested, provide a sufficient restoration of male fertility of the F1 crosses with majority of the P lines. The new restorer, 330 R appeared to be more effective in restoration of pollen fertility than the other currently used lines